Cepharanthine action in preventing obesity and hyperlipidemia in rats on a high-fat high sucrose diet - Adnan Iqbal; Rahila Najam; Shabana Simjee; Azfar Athar Ishaqui; Salman Ashfaq Ahmad; Zeeshan Ahmed; Shayan Ahmed; Salman Ahmed; Lailoona Jaweed; Madiha Maboos; Mir Muhammad Uzairullah; Suleha Jabeen; et al. (Saudi Pharmaceutical Journal, 2022)
Background: It was demonstrated that cepharanthine (CEP), derived from Stephania cepharantha hayata, is a potent inhibitor of the ABCC10 transmembrane protein. It is approved to be a natural product or remedy. The present study focuses on investigating whether cepharanthine effectively reduces hyperlipidemia and obesity in an experimental hyperlipidemic rat model. Method: Four groups of Wistar rats were assigned randomly to the following groups: a high-fat high sucrose diet (HFHS), normal-fat diet (NFD), HFHS plus cepraranthine (10 mg/kg) (HFHS-C), and a HFHS diet with atorvastatin (HFHS-A). The responses of rats were observed on the basis of serum and hepatic biochemical parameters, food intake, and body weight after CEP treatment, and assessing the histopathological modifications by the optical microscope in the liver and its cells. Results: Significant improvement in the serum total cholesterol (TC), serum triglycerides (TG), and serum low-density lipoprotein (LDL) levels were observed following CEP treatment. We have also observed significant improvement in the structure of liver tissue and reduced-fat droplets in the cytoplasm. Moreover, CEP had a significant effect in preventing the gain in body weight of animals, and food intake was not significantly affected. Conclusion: Our research results revealed that CEP significantly improved dyslipidemia and prevented the accumulation of fatty deposits in the rats' liver tissue fed an HFHS diet. In addition, CEP exerted an anti-obesity effect.